Home dispossession: the uneven geography of evictions in Palma (Majorca) - Vives-Miró, Sònia; González-Pérez, Jesús M.; Rullan, Onofre (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
Affordable housing, either owner-occupied or rented, is regarded as a key element of social reproduction. However, processes of housing commodification and financialization have increasingly resulted in precariatization of the population and the loss of the right to housing. In the Spanish case, neoliberal policies geared to the revalorization of built environments had caused a housing bubble of historical magnitude. Since it burst, a large number of households have been dispossessed of housing, clearly reflected in the avalanche of foreclosures and evictions that hit Spanish cities as the crisis unfolded. This paper focuses on the urban area of Palma (Majorca) by analyzing the foreclosures exerted on homeowners and the evictions of tenants who, from the start of the crisis of 2008, have not been able to afford their mortgage payments or rents. These evictions and foreclosures are correlated with the social status of the urban areas affected. The results show that the increase of evictions and foreclosures has emerged unevenly around the city. While tenant evictions have affected all types of urban areas, foreclosures have become much more evident in urban areas of low social status.